The emergence of social order in everyday interacting: re-conceptualizing a venerable sociological concept in light of conversation analysis - Arundale, Robert B. (Frontiers in Sociology, 2023)
For more than a century social theorists have asked how order at the macro-social level is related to human activity at the micro-social level. Among their answers are accounts of macro-level social order as emerging in micro-level relations among individuals. Sawyer's account of macro-level emergence in micro-level interaction rests on the individual's understandings of interactional frames. However, Rawls draws on Garfinkel and Sacks to argue that sociologist's accounts of the macrolevel interaction order need to be grounded in observable, micro-level social practices, instead of using conceptual abstractions like frames. Arundale's Conjoint Co-constituting Model of Communicating is grounded in research on observable social practices in Conversation Analysis, and offers an account of the emergence, in particular episodes of everyday interacting, of properties that define micro-level social systems. That account provides the basis for an account of the emergence, in recurrent micro-level interacting over time and space, of properties that define macro-level social systems. The basic idea is not new: what is new is accounting for the emergence of macro-level social order in terms of the recurrent emergence of micro-level social order as participants engage observable social practices in everyday interacting. Re-conceptualizing the emergence of macrosocial order addresses sociology's longstanding puzzlement regarding the macro-micro link, and points to needed research.